ISLAMIC MARKETING MIX STRATEGY IN INCREASING THE PRODUCTIVE BUSINESS OF TRUBUS IMAN ISLAMIC BOARDING SCHOOL - Ariani, Luthfiyah Nur; Mahrus, Moh; Parlina, Tika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Marketing strategy is the main foundation in business planning to guide sales, product distribution, and survive in competition. This research examines the Islamic marketing mix strategy at the Trubus Iman Islamic Boarding School, which has successfully integrated religious education with entrepreneurship, and won an award for economic independence. Using the 9P model which includes Product, Price, Promotion, Place, People, Process, Physical Evidence, Promise, and Patience, this research aims to determine the application of this strategy in increasing the productive business of Islamic boarding schools, as well as identifying the obstacles faced and their solutions. This research uses descriptive qualitative methods with data collection techniques through field observations, interviews and documentation. The research results show that the Trubus Iman Islamic Boarding School has implemented Islamic marketing concepts in every aspect of its marketing mix, such as quality halal products, fair prices, honest promotions, easy to reach distribution locations, and strict production supervision. However, the aspects of promotion and distribution through online stores such as Shopee and Tokopedia are still not optimal. Obstacles faced include high production of fresh products which exceeds market demand, lack of public awareness of the products, and high operational costs which cause product prices to increase. Efforts made to overcome this obstacle include product diversification, expanding marketing networks, and opening distributors in various regions.